Impact of Case Based Learning on Teaching of Undergraduate Oral Pathology Course - Shrestha, Bijayata; Subedi, Sushil; Paudel, Sabita; Subedi, Nuwadutta; Parajuli, Umesh (Journal of Nepal Health Research Council, 2023)
Background: Oral Pathology curriculum is taught as didactic lectures which promotes rote learning. This study intends to introduce and assess the impact of Case based Learning in student’s performance and to obtain the perception of students towards it. Methods: This cross-sectional study was conducted from March 2021 to January 2022 among dental undergraduate students (N=25) of Gandaki Medical College, Pokhara. The syllabus of Potentially Malignant Oral Lesions and Oral Cancer were covered for BDS third year students by didactic lectures, followed by Case Based Learning sessions (session I- Oral Leukoplakia, session II- Oral Squamous Cell Carcinoma). A pre-test and post-test, containing Multiple Choice questions relevant to the topics, were administered before and after the interventions. Students’ perceptions were collected using feedback questionnaire. The scores obtained in the pre and post-test were compared by Wilcoxon pair test and Mann Whitney U test. The level of significance was set at p <0.05. Results: Twenty and 21 students participated in session I and II respectively, and all (100%) of them felt that the case scenarios made the subject more interesting, and 19 (90.5%) students felt more such sessions should be added and be used along with lectures. Post test score after case-based learning was significantly higher (For Oral Leukoplakia p=0.028, for Oral Squamous Cell Carcinoma p<0.001) in comparison to didactic lectures. Conclusions: As case-based learning was positively perceived and preferred along with lectures, an attempt to incorporate it along with lectures in clinically important topics should be made. Keywords: Case based learning; dental undergraduate students; lecture; medical education; oral pathology